Estimations for aggregate amount of claims in a risk model with arbitrary dependence between claim sizes and inter-arrival times - Weiwei Ni; Chenghao Xu; Kaiyong Wang (AIMS Mathematics, 2022)
This paper considers a compound risk model, in which the individual claim sizes and their inter-arrival times can be arbitrarily dependent. We mainly investigate the claim sizes are extended negatively dependent. When the claim sizes have consistently-varying-tailed distributions, we obtain precise large deviations of the aggregate amount of claims in the above dependent compound risk model.